Intangible values and tourists’ motivations: the case of the Pahang National Park - Ching, Fei Ern; Goh, Hong Ching (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Protected areas are fast becoming tourist attractions and as such have contributed increasingly to nature-based tourism , the industry’s fastest growing sector. It is assumed that tourists visiting the protected areas are motivated by intangible values such as recreational, cultural and spiritual, educational, artistic and aesthetic, and existential values. This paper presents the findings of a study aimed at examining the kind of intangible values that had motivated tourists to the Pahang National Park (Taman Negara Pahang, TNP). A total of 341 samples was collected from a questionnaire survey involving both local and international tourists of the TNP. Results of the analyses revealed that tourists to TNP were generally motivated by particular recreational values (‘to exercise’), cultural values (’to understand indigenous people’s lifestyle’), educational values (‘to recognize and gain knowledge about the local flora and fauna ‘), artistic and aesthetic values (‘to show concern with the existence of natural environment’). As for the park existential values, local and international tourists demonstrated different perceptions. Most local tourists were not willing to pay more for park’s entrance fee as compared to the international tourists. Both parties , nevertheless, were willing to pay more if it was to be used for nature conservation purposes.